The telecom value chain, opportunities and revenues created by the nigerian telecom boom - Nsikan Nkordeh; Uzairue Stanley Idiake; Ibinabo Bob-Manuel; Francis Anyasi (Institute of Advanced Engineering and Science, 2019)
In Nigeria today, we face a serious economic challenge which is as a result of our swindling primary source of revenue (oil), there is fear amongst our economists which is can Nigeria bounce back to what she once was? Can there be an alternative source to serve as a buffer to what we already have. This study aims to bring to prime focus, an industry which has begun blooming in the background. Despite the publicity and popularity enjoyed by today’s telecom giants in the country, there is very little knowledge pertaining to the tremendous impact that it has had directly or indirectly on our economy over the years. Since the liberalization of the telecom industry that brought about the involvement of private investors into the sector, the opportunities and revenues generated has brought about a tremendous effect on the economy. The telecom sector is only second after the oil and gas industry in the amount of finance it contributes to the federal account. This paper discusses some of the value chains, opportunities, revenue that the telecom industry has brought to Nigeria. It uses data obtained from relevant authorities.